2007
DOI: 10.1002/jcb.21605
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational unloading induces an anti‐angiogenic phenotype in human microvascular endothelial cells

Abstract: Creating conditions similar to those occurring during exposure of cells to microgravity modulates endothelial functions. We have previously demonstrated that human macrovascular endothelial cells in simulated hypogravity proliferate faster than controls, partly because they downregulate interleukin 1alpha. On the contrary, murine microvascular endothelial cells are growth inhibited in simulated hypogravity, and this is due, at least in part, to the decrease of interleukin 6. Since endothelial cells are very he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 28 publications
3
43
1
Order By: Relevance
“…Accordingly, we demonstrated the different response to simulated microgravity of these cells. 14,16 There is one interesting similarity in the behavior of these cells, i.e. the production of ROS dramatically drops when HUVECs and HDMECs are confluent, thus indicating an inverse correlation between cell number and ROS generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we demonstrated the different response to simulated microgravity of these cells. 14,16 There is one interesting similarity in the behavior of these cells, i.e. the production of ROS dramatically drops when HUVECs and HDMECs are confluent, thus indicating an inverse correlation between cell number and ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…Simulated microgravity affects endothelial function and different responses to gravitational unloading have been described in micro-and macrovascular human endothelial cells. [13][14][15][16] We have also shown that microvascular endothelial cells in simulated microgravity release proteins that affect osteoblast behavior in a co-culture system. 17 Recently, both macrovascular 18 and microvascular endothelial cells were flown to the International Space Station (ISS), which offers unique opportunities to study the effect of space on the cells.…”
mentioning
confidence: 99%
“…Mariotti and Maier reported that only microvascular cells suffer from inhibited growth and angiogenesis, while macrovascular cells proliferated faster when grown on an RWV. 103 Exposing the cells to altered gravity conditions on an RPM led an increased apoptosis rate, 17,53 which was significantly reduced by the addition of vascular endothelial growth factor to the culture medium. 104 Similar effects have also been reported in further studies.…”
Section: 83mentioning
confidence: 99%
“…Nevertheless, it is necessary to study the functions activated by spontaneous Ca 2+ oscillations in cerebral arteries, and especially the molecular targets implicated in the proliferation/apoptosis balance, such as transcription factors observed in endothelial cells [25], and also the Ca 2+ sensitivity of myofilaments. Finally, this adaptation appeared to have settled rapidly in 1 week and could persist during 28 days [49,51], yet the time course of the molecular adaptation as well as the effect of a longer exposure to HU and μG remain to be further evaluated.…”
Section: Perspectivesmentioning
confidence: 99%